Hubungan Pemberian Asi Eksklusif Dengan Status Gizi Bayi Usia 6 Bulan Di Wilayah Kerja Puskesmas Sabrang - Wenny Diah Kurniasari; Rifzul Maulina (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Introduction: Lack of nutrition at an early age can lead to impaired child growth and development. Efforts have been made to overcome nutritional problems, one of which is through exclusive breastfeeding. The study aims to determine the relationship between breastfeeding and the nutritional status of infants aged 6 months in the Sabrang Health Center Working Area. Research Methods: This study used a cross sectional research design, with a sample of 30 babies. Sample. Data research was test used was the chi-square test aimed at finding the correlation of two variables. Research Results: After conducting research conducted on 30 infants, statistical tests using the Chi Square test showed a p value of 0.031 <0.05. Conclusion: So that there is a significant relationship with exclusive breastfeeding with the nutritional status of infants aged 6 months in the Sabrang Health Center Working Area.